Aggressive central giant cell granuloma - A case series with literature review - Manjula Hebbale; Versha Rani Giroh; Amit Mhapuskar; Darshan Hiremutt (Wolters Kluwer Medknow Publications, 2019)
Central giant cell granuloma (CGCG) of the maxillofacial region is generally present as an asymptomatic slowly growing localised disease to aggressive neoplasm-like rapid expansive progression typically present with localised disease. It is an uncommon benign lesion with a low incidence that occurs in the craniofacial region especially in jaw bones. It is a localised osteolytic lesion with varied biologic behavior of aggression which affects the jaw bones. There is much controversy regarding it arising as a result of trauma and its connection with the giant cell lesion seen in the long bones. As it is uncommon, it does not possess any characteristic clinical or radiologic features and resembles neoplasms; the diagnosis is initially some odontogenic or non-odontogenic neoplasm till a definitive histologic diagnosis of CGCG is made. We report five cases of an aggressive form of CGCG at different sites of involvement in the jaw bones.